Advancements in staging and imaging for penile cancer. Issue 6 (November 2017) - Ottenhof, Sarah R.; Leone, Andrew R.; Horenblas, Simon; Spiess, Philippe E.; Vegt, Erik
Abstract : Purpose of review: We review recent advancements in staging and imaging of penile cancer, including surveillance after therapy. Recent findings: For cN0 patients, the sentinel lymph node biopsy is currently considered the preferred way for invasive staging. It has largely replaced other modalities such as staging inguinal lymphadenectomy. Its diagnostic value increases when combined with other staging modalities such as ultrasound with fine-needle aspiration cytology (US-FNAC) or fluorodeoxyglucose-PET with computed tomography (PET/CT). In patients with palpably suspicious nodes (cN+), imaging is more useful. PET/CT has shown good accuracy in a limited number of small studies. US-FNAC can confirm nodal metastatic disease. A staging inguinal lymphadenectomy is of therapeutic value but is associated with significant morbidity. Omitting staging inguinal lymphadenectomy was recently described; one study showed well tolerated use of sentinel lymph node biopsy combined with intraoperative ultrasound-guided resection of suspicious nodes in cN+ patients. Therapeutic inguinal lymphadenectomy was only performed in the 42% of groins with metastases confirmed by disorder. For M-staging, PET/CT has shown good sensitivity, and its role should be further evaluated. Follow-up and surveillance rely on physical examination and US-FNAC. Summary: Over the past decade, staging and treatment of penile cancer have become less invasive, while survival tends to improve.